Hot spot 19F magnetic resonance imaging of inflammation. (7th May 2020) - Bouvain, Pascal; Temme, Sebastian; Flögel, Ulrich
Abstract: Among the preclinical molecular imaging approaches, lately fluorine ( 19 F) magnetic resonance imaging (MRI) has garnered significant scientific interest in the biomedical research community, due to the unique properties of fluorinated materials and the 19 F nucleus. Fluorine is an intrinsically sensitive nucleus for MRI—there is negligible endogenous 19 F in the body and, thus, no background signal which allows the detection of fluorinated materials as "hot spots" by combined 1 H/ 19 F MRI and renders fluorine‐containing molecules as ideal tracers with high specificity. In addition, perfluorocarbons are a family of compounds that exhibit a very high fluorine payload and are biochemically as well as physiologically inert. Perfluorocarbon nanoemulsions (PFCs) are well known to be readily taken up by immunocompetent cells, which can be exploited for the unequivocal identification of inflammatory foci by tracking the recruitment of PFC‐loaded immune cells to affected tissues using 1 H/ 19 F MRI. The required 19 F labeling of immune cells can be accomplished either ex vivo by PFC incubation of isolated endogenous immune cells followed by their re‐injection or by intravenous application of PFCs for in situ uptake by circulating immune cells. With both approaches, inflamed tissues can unambiguously be detected via background‐free 19 F signals due to trafficking of PFC‐loaded immune cells to affected organs. To extend 19 F MRI tracking beyond cells with phagocytic properties, the PFC surface can further be equipped with distinct ligands to generate specificity against epitopes and/or types of immune cells independent of phagocytosis. Recent developments also allow for concurrent detection of different PFCs with distinct spectral signatures allowing the simultaneous visualization of several targets, such as various immune cell subtypes labeled with these PFCs. Since ligands and targets can easily be adapted to a variety of problems, this approach provides a general and versatile platform for inflammation imaging which will strongly extend the frontiers of molecular MRI. This article is categorized under: Diagnostic Tools > in vivo Nanodiagnostics and Imaging Therapeutic Approaches and Drug Discovery > Emerging Technologies Therapeutic Approaches and Drug Discovery > Nanomedicine for Cardiovascular Disease Abstract : Labelling approaches for 19 F MRI